A Study on the Factors Influencing the Insurance Coverage of the Girl Child in India: An Empirical Study - D’Silva, Bernadette; D’Silva, Stephen; Bhuptani, Roshni Subodhkumar (Indian Journal of Marketing, 2011)
There is no doubt that India has made tremendous progress in the midst of globalization. But the status of women in India is a sort of a paradox. On the one hand, she has achieved pinnacles of success, but on the other hand, she is deprived of the power for taking independent decisions about her career and life. The key reason behind this is that the majority of females in India still do not possess financial autonomy. Insurance is one of the fastest growing sectors in India. But the percentage of females insured, especially, the insurance cover for the young girls is very less. The research paper, therefore, has basically identified those parameters that are considered to be important for purchasing the insurance cover of the girl child. Hypotheses developed in the study have revealed that there are many socio-economic factors, which influence the insurance coverage of the girl child with respect to the purpose and type of insurance policy taken. Finally, the paper brings into light various recommendations for the Indian society and has stressed more on the Government’s role in providing safe and secured future to the girls in India.